VIOLATION OF MAXIM ON FACEBOOK STATUS OF UNIVERSITY STUDENTS IN NORTH SUMATERA - Tesha Lidia Aritonang and Meisuri (LINGUISTICA, 2015)
This study deals with violation of maxin on facebook status. The objectives of thestudy were to find out the types of maxim which were violated by university studentsand described the reasons why they did it in the conversation. The study used Gricetheory of conversational maxim and was conducted by using qualitative descriptivedesign which aimed at describing the types of violated maxim and the reasons whypeople did it. The data were the utterances and were taken from fifty selectedstatus of students from 9 universities in North Sumatera and collected byrandomly sampling technique. The findings of the study showed there were threetypes and reasons of using violation of maxim. They were maxim of quality (1),maxim of quantity (17), maxim of relation (24) and as the most dominant type. Theirreasons were to show respect, change a topic and create humor.